Pengaruh Scripless Trading Pada Kepemilikan Saham Ditinjau Dari Perspektif Hukum Perdata Di Indonesia - Crisdiant, Ellyn; Wibowo, Nadya Priscilla (WARKAT, 2024)
The changing of stock trading system that becomes scripless trading, it made the  physical paper certificate as past form of ownership stock changes into electronic data in form of data bill effect. In other side, the ownership verification of lawsuit at court in Procedure of Civil Law manner has decided the form of evidence that can be submitted in the civil lawsuit, one of them is the evidence that appropriate with the early form of stock ownership. After the announcement of Regulation number 11-year 2008 about Information and Electronic Transaction (ITE Regulation) indeed enable to make information and electronic transaction could bind over in law manner. This paper uses juridical conclude that the Regulation number 8 year 1995 about Capital Market in this case is Lex Specialis derogate Lex Generali from KUHD, KUH Perdata, 2 Regulation number 40 year 2007 about Limited Company, in relation with the clause that arrange about stock which is being traded in capital market, and the electronic data and its prints that being obtained from scripless trading transaction through the existing trading network electronic system is recognized as the legal evidence also admitted as the evidence  in the court.